Cheek‐to‐cheek: Communal nesting in an ephemeral pool‐breeding frog. (19th September 2022) - Gould, John; Clulow, John; Clulow, Simon
Abstract: Communal nesting is a behaviour exhibited by some oviparous species, the adults of which deposit their eggs over the same time period in a common area and possibly in direct physical contact. While this may occur inadvertently, it is proposed to be an adaptive trait in some species. Herein, we describe both solitary and communal nesting behaviours in the sandpaper frog ( Lechriodus fletcheri ). Field observations over two consecutive breeding seasons revealed that adults of this species frequently deposit their eggs in frothed nests alongside those of other mating pairs to form floating communal rafts or "masses" on the surface of the water. The presence of communal masses despite; (i) the relatively small number of nests deposited within each breeding episode and (ii) the space available for nests to be deposited separately within a pool, both indicate that some adults are deliberately choosing to lay their nests together. We propose that adults are thus engaging in a form of social behaviour and that communal nesting may be highly advantageous for improving offspring survival by complimenting the anti‐predator properties of the froth nest. This is because the communal mass further isolates embryos from the external environment during development prior to hatching, given a reduction in the surface area relative to volume of each nest that composes the mass. While future research is required to determine why both solitary and communal nesting behaviours are exhibited in this species, it could suggest that there are certain costs associated with communality that occasionally outweigh the benefits. Abstract : Depositing eggs in the same location or even in direct physical contact is referred to as communal egg‐laying or nesting and may confer adaptive benefits for oviparous species. We show that adult sandpaper frogs ( Lechriodus fletcheri ) frequently deposit their eggs in frothed nests alongside those of other mating pairs to form communal masses. We propose that this is a social behaviour that is advantageous for offspring by protecting them from the threat of cannibalism by previously hatched conspecific tadpoles.